Comics and conflict : patriotism and propaganda from WWII through Operation Iraqi Freedom - Scott, Cord A. (Naval Institute Press, 2014)
"The comic book, which emerged in its modern form in the 1930s, was initially a form of simple, visual entertainment that gave readers, especially children, a form of escape from daily life. However, as World War II began, comic books evolved into a form of propaganda, providing information and education for both children and adults. Comics and Conflict examines how comic books were used to display patriotism, valor and adventure through war stories, and eventually to tell of the horrors of combat from World War II through the current conflicts in Iraq and Afghanistan"--